Plasma-assisted reduction of supported metal catalyst using atmospheric dielectric-barrier discharge - Kim, SS; Lee, H; Na, BK; Song, HK (ELSEVIER SCIENCE BV, 2004)
Methane conversion was carried out in a presence of a catalyst within a dielectric-barrier discharge reactor. Temperature programmed reduction (TPR) and plasma-assisted reduction (PAR) was studied to reduce the supported metal catalysts. Prepared catalyst was successively reduced by PAR. The selectivity Of C2H6, C2H4 and C2H2 was higher among the produced hydrocarbons when the methane conversion was carried out in the absence of a catalyst. In the presence of Pt and Co catalyst, the main products of plasma catalytic reaction were light alkanes such as C2H6, C3H8 and C4H10. The plasma catalytic reaction showed positive characteristics to produce light alkanes when Pt and Co catalyst were used after PAR. PAR was an effective method to reduce supported metal catalyst. (C) 2003 Elsevier B.V. All fights reserved.
Keywords: HIGHER HYDROCARBONS; METHANE CONVERSION; OXIDATIVE DIMERIZATION; CORONA DISCHARGE; OXIDE; TEMPERATURE; REACTOR; CH4